THE EFFECT OF FICTION SHORT MOVIE ON STUDENTS’ ENGLISH SPEAKING ABILITY - Riswanto Riswanto; Reko Serasi; Azzah Salandega; Kasmaini Kasmaini (English Review: Journal of English Education, 2022)
The purpose of this research is to investigate whether or not students' students' speaking skills may be improved by watching short films. Quantitative research using a quasi-experimental design is the method that was used for the study. All of the pupils in the second grade at SMP A'isyiyah Pagaralam in South Sumatra, Indonesia, make up the population. This research was conducted with the participation of forty different students. It was decided that 20 students from Class A would make up the experimental group, and the remaining 40 students from Class B would serve as the control group. The method of data analysis makes use of a prerequisite test, specifically the normality test and the homogeneity test, and the final test is hypothesis testing. According to the findings of the research that was carried out, there is an effect in the use of short movies as a medium for improving students' speaking ability.